2010
DOI: 10.1073/pnas.0910141107
|View full text |Cite
|
Sign up to set email alerts
|

The KaiA protein of the cyanobacterial circadian oscillator is modulated by a redox-active cofactor

Abstract: The circadian rhythms exhibited in the cyanobacterium Synechococcus elongatus are generated by an oscillator comprised of the proteins KaiA, KaiB, and KaiC. An external signal that commonly affects the circadian clock is light. Previously, we reported that the bacteriophytochrome-like protein CikA passes environmental signals to the oscillator by directly binding a quinone and using cellular redox state as a measure of light in this photosynthetic organism. Here, we report that KaiA als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 34 publications
7
71
0
1
Order By: Relevance
“…Thus, natural variation in biosynthetic enzymes can feedback to alter circadian clock output, suggesting that the flow of information flow between the clock and metabolism is bidirectional. Similar links between clock function and metabolism have been previously reported (Rutter et al, 2002;Dodd et al, 2007;Duez and Staels, 2008;Kovac et al, 2009;Wood et al, 2010). Interestingly, we found that two completely separate genomics technologies, transcriptomics and metabolomics, that measure separate products, transcripts, and metabolites, independently identify the same genetic network within this Arabidopsis population.…”
Section: Plant Metabolism and Circadian Clock Outputssupporting
confidence: 56%
“…Thus, natural variation in biosynthetic enzymes can feedback to alter circadian clock output, suggesting that the flow of information flow between the clock and metabolism is bidirectional. Similar links between clock function and metabolism have been previously reported (Rutter et al, 2002;Dodd et al, 2007;Duez and Staels, 2008;Kovac et al, 2009;Wood et al, 2010). Interestingly, we found that two completely separate genomics technologies, transcriptomics and metabolomics, that measure separate products, transcripts, and metabolites, independently identify the same genetic network within this Arabidopsis population.…”
Section: Plant Metabolism and Circadian Clock Outputssupporting
confidence: 56%
“…Ectopic introduction of oxidized quinones can entrain the clock both in vivo and in vitro, and both KaiA and CikA play roles related to entrainment through binding of their PsR domains to oxidized quinones (71,72,(76)(77)(78). The aggregation state and/or stability of the proteins is affected by quinone binding in vivo (71,77). Still, the precise mechanism by which quinone binding influences the PTO is not currently well-understood.…”
Section: Metabolic Of Entrainment Of the Clockmentioning
confidence: 99%
“…As a result, the concentration of oxidized quinones rises rapidly but briefly when photosynthesis shuts down with the onset of darkness before other pathways restore the redox steady state (76). Ectopic introduction of oxidized quinones can entrain the clock both in vivo and in vitro, and both KaiA and CikA play roles related to entrainment through binding of their PsR domains to oxidized quinones (71,72,(76)(77)(78). The aggregation state and/or stability of the proteins is affected by quinone binding in vivo (71,77).…”
Section: Metabolic Of Entrainment Of the Clockmentioning
confidence: 99%
See 1 more Smart Citation
“…The clock synchronizes to the environment through KaiA and a histidine protein kinase, CikA. Both proteins bind quinone cofactors, likely plastoquinone present in the photosynthetic membrane, that reflect the cellular redox state (12,13). KaiC activity also is modulated by the cellular ATP/ADP ratio (14), and both the cellular redox state and ATP/ADP ratio are dependent on the availability of external light.…”
mentioning
confidence: 99%